Trump II and US nuclear assurances to NATO: Policy options instead of alarmism - Liviu Horovitz; Elisabeth Suh (Stiftung Wissenschaft und Politik (SWP), 2024)
While a second Trump Presidency would be challenging for transatlantic ties, US nuclear assurances to its NATO allies in Europe would likely be the last casualty - not the first - of a fraying relationship. There is an intrinsic incompatibility between the United States completely abandoning its role as global actor, which would be the prerequisite for the withdrawal of such assurances, and Trump's domestic interests. It cannot be denied that the worst-case scenario - namely, the end of extended nuclear deterrence - is possible and requires careful contingency planning on the part of the allies; but it is highly unlikely and should not distract from addressing the more probable outcome. Even in the best-case scenario of a Trump II administration resembling his first term, US nuclear assurances are likely to become less credible. To allay concerns, German and European policymakers should work with their US counterparts before and after the November 2024 election to strengthen transatlantic diplomatic coordination, conventional deterrence and defence, as well as nuclear options.
Keywords: 320; Trump Presidency; NATO; Europe; nuclear assurance; nuclear deterrence; European security